Cloning and expression analysis of juvenile hormone epoxide hydrolase-like (EsJHEH-like) from Eriocheir sinensis, and its potential roles in methyl farnesoate metabolism. Issue 1 (2nd January 2022) - Chen, Tiantian; Diao, Yingzhu; Xu, Ruihan; Sheng, Na; Liu, Fan; Xie, Qiming; Su, Shiping; Ma, Keyi; Li, Xilei
ABSTRACT: The sesquiterpenoid methyl farnesoate (MF), a crustacean equivalent of juvenile hormone (JH III), plays important roles in regulating many physiological processes in crustaceans, especially ovarian development and reproduction. Previous research indicates that degradation of MF in crustaceans is similar to JH III degradation, and involves specific carboxylesterases. Juvenile hormone esterase hydrolase (JHEH) is another important enzyme responsible for JH inactivation in insects. In this study, the full-length cDNA of EsJHEH-like was identified and characterized in Eriocheir sinensis. Sequence analysis showed that EsJHEH-like belongs to the microsomal epoxide hydrolase (mEH) family containing several typical motifs. Quantitative PCR results showed that EsJHEH-like was expressed primarily in the hepatopancreas. During ovarian development, EsJHEH-like mRNA expression in the hepatopancreas was elevated specifically in the early vitellogenic stage, prior to the remarkable rise in haemolymph MF titre reported in previous studies, but no significant changes in the ovary. In addition, EsJHEH-like expression in the hepatopancreas was notably greater than in the ovary at each stage except for previtellogenic oocytes. Furthermore, EsJHEH-like expression in the hepatopancreas was significantly induced in vitro and in vivo, but not in the ovary. Taken together, these results suggest that EsJHEH-like may potentially serve as an MF hydrolase involved in the degradation of MF.